Misspellings Analysis in the Heritage Learners´ Writing - Contreras-Wise, Ángela Cristina (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Constant exposure to one or more words involves developing the skill to mentally represent the phonological form of a word spoken in a precise way. This skill is grown throughout the years of schooling by being in contact with that language. However, Spanish heritage learners in USA have not been schooled enough in that language during those years when such acquisition is essential. Those students retake the schooling of the language at the university, where they seek to learn orthography to prepare academically and professionally (Beaudrie & Ducar, 2005).   This work compares frequency and typology of misspellings in 40 essays which are classified in four levels. The aim is to identify the level with the most misspellings and the category and morpheme with the highest frequency of errors produced by this group of students. Results confirm what is expected: the higher the level, the lower the percentage of misspellings.